Tumor-Associated Macrophages in Oncolytic Virotherapy: Friend or Foe? - Denton, Nicholas L. (Biomedicines, 2016)
Cancer therapy remains a challenge due to toxicity limitations of chemotherapy and radiation therapy. Oncolytic viruses that selectively replicate and destroy cancer cells are of increasing interest. In addition to direct cell lysis, these vectors stimulate an anti-tumor immune response. A key regulator of tumor immunity is the tumor-associated macrophage population. Macrophages can either support oncolytic virus therapy through pro-inflammatory stimulation of the anti-tumor response at the cost of hindering direct oncolysis or through immunosuppressive protection of virus replication at the cost of hindering the anti-tumor immune response. Despite similarities in macrophage interaction between adult and pediatric tumors and the abundance of research supporting macrophage modulation in adult tumors, there are few studies investigating macrophage modulation in pediatric cancers or modulation of immunotherapy. We review the current state of knowledge regarding macrophages in cancers and their influence on oncolytic virotherapy.